Leaves from tropical trees as protein supplements in diets for sheep - Wiegand, R.O.; Reed, J.D.; Combs, D.K.; Said, A.N. (1996)
The effects of forage supplement and level of maize grain (Zea mays L.) offered on intake, digestibility, N balance, and rate of gain were determined for rams fed teff straw (Eragrostis abyssinica). Supplements (leaves from five trees, Faidherbia albida, Carissa edulis, Dichrostachys cinerea, Leucaena leucocephala, and Sesbania sesban, or chopped alfalfa hay, Medicago sativa) provided 40 g per day of crude protein. Maize grain was supplemented to half of the sheep at 100 g per day. Rams fed leaves of F. albida, L. leucocephala, S. sesban, and the alfalfa hay gained 49 g per day with maize and 23 g per day without maize. Higher content of proanthocyanidins and related polyphenols in F. albida had no detrimental effect on N balance and rate of gain (P < 0.05) in comparison to alfalfa. The high content of proanthocyanidins and related polyphenols in C. edulis and D. cinerea resulted in low intake, digestibility, and rate of gain (6 g day-1) when fed with maize, and high weight loss (-63 g day-1) without maize.